2014
DOI: 10.1111/bjd.12845
|View full text |Cite
|
Sign up to set email alerts
|

Genetic polymorphisms in the methylenetetrahydrofolate reductase gene (MTHFR) and risk of vitiligo in Han Chinese populations: a genotype-phenotype correlation study

Abstract: SummaryBackground Recent evidence has revealed an elevation of total homocysteine (tHcy) in patients with vitiligo. Methylenetetrahydrofolate reductase (MTHFR) is one of the main enzymes regulating homocysteine (Hcy) metabolism. Thus, polymorphisms of MTHFR could potentially contribute to the development of vitiligo by affecting MTHFR activity and tHcy levels. Objectives To evaluate the potential association between MTHFR polymorphisms and vitiligo susceptibility. Methods In total, 1000 patients with vitiligo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
31
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 42 publications
1
31
0
1
Order By: Relevance
“…Further, the findings reported by Chen et al . are supported by the previous functional study of the MTHFR 1801133 SNP, which showed that both homozygous and heterozygous rs1801133 variants exhibited high levels of MTHFR enzyme activity and rescued the biochemical phenotype of the MTHFR knockout cells …”
supporting
confidence: 65%
See 2 more Smart Citations
“…Further, the findings reported by Chen et al . are supported by the previous functional study of the MTHFR 1801133 SNP, which showed that both homozygous and heterozygous rs1801133 variants exhibited high levels of MTHFR enzyme activity and rescued the biochemical phenotype of the MTHFR knockout cells …”
supporting
confidence: 65%
“…Vitiligo has been the subject of debate involving several hypotheses, oxidative stress being a major contributor for melanocyte cell death . Among the significant candidate genes for vitiligo Chen et al . followed an important gene methylenetetrahydrofolate reductase ( MTHFR ) by functionally correlating its variants with its enzyme activity and total homocysteine (tHcy) levels.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The results of the current study were in agreement with previous studies that proved an association between MTHFR gene polymorphism and various chronic inflammatory diseases, including psoriasis, Behcet's disease and vitiligo …”
Section: Discussionmentioning
confidence: 62%
“…The results of the current study were in agreement with previous studies that proved an association between MTHFR gene polymorphism and various chronic inflammatory diseases, including psoriasis, Behcet's disease and vitiligo. [24][25][26] The results of the present study revealed that folate deficiency and hyperhomocysteinemia have been associated with the TT mutant genotype. However, these findings were not significant (P>.05).…”
Section: Discussionmentioning
confidence: 90%